Adoption of Cashless Payments by Retail Enterprises in Legazpi City - Jacob, Dahna Mae (Journal of Interdisciplinary Perspectives, 2024)
This study examined the adoption of cashless payment methods among retail businesses, identifying the types of payment methods utilized, the factors influencing their adoption, and the challenges retailers face. Data were collected through interviews with 50 retail owners and managers. Results indicate that mobile wallets, particularly GCash, are the most frequently used cashless payment method, followed by debit/credit cards and online banking. Factors driving adoption include ease of use, trust and security, and social influence. However, retailers need to work on technological complexities, customer expectations, limited cash-in and cash-out facilities for mobile wallets, and financial costs from banks and fintech companies. The study concludes that enhanced infrastructure and support are essential for the region's broader adoption of cashless payments. The findings underscore the crucial role of policymakers and financial institutions in addressing these barriers to foster a more inclusive and efficient cashless economy.